Path Analysis on the Biopsychosocial Factors Associated with Hypertension - Febry Istyanto; Ambar Mudigdo; Setyo Sri Rahardjo (Journal of Epidemiology and Public Health, 2019)
Background: Hypertension is a non-communicable disease which may lead to premature death and disability. This study aimed to determine the biopsychosocial factors associated with the risk of hypertension.Subjects and Method: This was an analytic observational study with a case-control design. This study was conducted at Dr. Moewardi Hospital, from September to November 2018. A sample of 225 patients was selected by fixed disease sampling. The dependent variable was hypertension. The independent variables were anxiety, stress, quality of sleep, body mass index (BMI), physical activity, vegetables and fruit, coffee drink, and soft drink consumption. Blood pressure was measured by sphygmomanometer. Body weight was measured by scale. Body height was measured by microtoise. The other data were collected by questionnaire and analyzed by path analysis.Results: Hypertension directly increased with anxiety (b= 0.26; 95%CI= 0.02to 0.51; p= 0.037), stress (b= 0.28; 95%CI= 0.04 to 0.53; p= 0.022), poor quality of sleep (b= 0.46; 95%CI= 0.06 to 0.87; p= 0.026), BMI (b= 0.68; 95%CI= 0.051 to 1.31; p= 0.034), coffee drink consumption (b= 1.31; 95%CI= 0.17 to 2.46; p= 0.024), and soft drink consumption (b= 0.38; 95%CI= 0.04 to 0.72; p= 0.029). Hypertension directly decreased with high physical activity (b= -0.04; 95%CI= -0.07 to -0.004; p= 0.027), vegetable and fruit consumption (b= -1.13; 95%CI= -2.07 to -0.19; p= 0.037). Hypertension was indirectly affected by anxiety, physical activity, quality of sleep, and coffe drink consumption through BMI and quality of sleep.Conclusion: Hypertension is directly and positively affected by anxiety, stress, poor quality of sleep, BMI, coffee drink consumption, and soft drink consumption, but negatively affected by high physical activity, vegetable and fruit consumption.Keywords: hypertension, biopsychosocial, determinantsCorrespondence: